(untitled) (CIPEEX, 2022)
MANAGEMENT IS UNDERSTOOD AS A MEDIATING, ARTICULATING, EVALUATIVE AND DECISION-MAKING ACTION, SOMETIMES CONSENTING OR NOT TO THE AUTONOMY OF THOSE INVOLVED. THIS IS AN INTEGRATIVE, DESCRIPTIVE AND QUALITATIVE REVIEW BASED ON READING AND SYNTHESES OF SCIENTIFIC REFERENCES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL). THE OBJECTIVE IS TO DEAL WITH SKILLS THAT COLLABORATE FOR THE EXERCISE OF MANAGEMENT AND LEADERSHIP OF NURSES. FLORENCE TAUGHT US HER ROLE AS AN EDUCATOR AND LEADER THROUGH HER CONCERN FOR PEOPLE’S HEALTH CARE. NURSES IN THE MANAGEMENT AND LEADERSHIP SCENARIO FACE REAL AND VITAL CHALLENGES RELATED TO PATIENT CARE AND INDIVIDUAL AND TEAM PERFORMANCE, SO THEY MUST BE PROACTIVE, ANALYZE AND PROMOTE EFFECTIVE, STIMULATING AND INNOVATIVE STRATEGIES FOR THE EXCELLENCE OF NURSING ACTIONS.